HUBUNGAN POLA KOMUNIKASI DAN LATAR BELAKANG PENDIDIKAN ORANGTUA TERHADAP HASIL BELAJAR PKN SISWA KELAS V (Universitas Negeri Semarang, 2018)
Problems in grade V elementary school show that, learning outcomes that are in very high category about 17%, high category about 42%, moderate category about 29%, and low category about 12%. Based on interview result with teacher the factors that affect Civics learning outcomes are communication pattern and parents’ education background. This study aims to examine the relationship between communication patterns and parental education background with the results of Civics learning. This research uses correlation method with quantitative approach. There are two independent variables, namely communication pattern and parents' education background, and the dependent variable is the result of Civics learning. The sample in this study using proportional random sampling technique with the sample size of 100 students. The methods are data collection using questionnaires, documentation, and tests. The results showed that: (1) There is a significant relationship between the communication pattern with the results of Civics learning with the result of the research obtained the significance level 0.000 <0.05. The correlation of 0.688; (2) There is a significant correlation between parents' education background to the result of Civics learning with the result of the research obtained by significance level 0,000 <0,05. The correlation of 0.633; (3) There is a significant correlation between communication pattern and parents' education background to the result of Civics learning with the result of the research obtained by the significance level 0.000 <0,05. The correlation of 0.724. For the large contribution among communication patterns and parents' educational background towards the student's learning outcomes for 52.4%.The conclusions of this study are to indicate a positive and significant relationship between communication patterns and parents' educational background with the results of Civics learning. Teachers and parents can motivate and improve good communication relationships towards students to improve students' learning spirits to achieve optimal learning outcomes.